"La visita del embajador de mexico sr. Tejeda a la colectividad de los campesinos de Barcelona, zonas de Pla de Marti". Left Tejeda with his daughter. Right Aguilar. Copied from CNT Collection. Series of 3 photos
"La visita del embajador de mexico sr. Tejeda a la colectividad de los campesinos de Barcelona, zonas de Pla de Marti". Left Tejeda with his daughter. Right Aguilar. Copied from CNT Collection. Series of 3 photos.